2012
DOI: 10.2131/jts.37.381
|View full text |Cite
|
Sign up to set email alerts
|

Trichloroethylene enhances TCR-CD3-induced proliferation of CD8<sup>+</sup> rather than CD4<sup>+</sup> T cells

Abstract: -Trichloroethylene (TCE) is suspected as a potent immunomodulator that accelerates the development of allergic diseases. We previously reported that TCE promotes ovalbumin (OVA)-induced active cutaneous anaphylaxis, including enhancing antigen-specific serum IgE levels and splenic lymphocyte proliferation. However, the target cells and molecular mechanism through which TCE modulates antigen-specific immune responses remain unclear. To identify a potential underlying mechanism, we investigated whether TCE modul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Previous reports have indicated that various environmental pollutants activate splenocytes (Koike et al ., , ; Kobayashi et al ., ). Our result showed ASD1 and ASD2 increased proliferation of splenocytes, although its detailed cellular contribution has not been established.…”
Section: Discussionmentioning
confidence: 97%
“…Previous reports have indicated that various environmental pollutants activate splenocytes (Koike et al ., , ; Kobayashi et al ., ). Our result showed ASD1 and ASD2 increased proliferation of splenocytes, although its detailed cellular contribution has not been established.…”
Section: Discussionmentioning
confidence: 97%
“…A Japanese team reported that TCE enhances TCR-CD3-induced proliferation of CD8 + rather than CD4 + cells and disrupts various activities of peripheral T cells in male Balb/c mice. 27 Li et al 28 showed that TCEexposed mice show a shift in Th1/Th2 and Th17/Treg ratios. 28 In addition, liver injury caused by immune sensitization through TCE is also mediated by activation of the complement system.…”
Section: Discussionmentioning
confidence: 99%
“…Cellular immunity and humoral immunity are also involved in TCEHS. A Japanese team reported that TCE enhances TCR‐CD3‐induced proliferation of CD8 + rather than CD4 + cells and disrupts various activities of peripheral T cells in male Balb/c mice 27 . Li et al 28 showed that TCE‐exposed mice show a shift in Th1/Th2 and Th17/Treg ratios 28 .…”
Section: Discussionmentioning
confidence: 99%
“…However, a limited understanding exists regarding the effects of ASD on other organs, including the lymphoid organs. Some reports have provided evidence indicating that various environmental pollutants can activate splenocytes (Kobayashi, Nakanishi, & Nagase, 2012;Koike, Inoue, Yanagisawa, & Takano, 2009). Honda et al showed that ASD increased splenocyte proliferation in vitro (Honda et al, 2013).…”
Section: Discussionmentioning
confidence: 99%